Ten years after - Gibbs, Philip, 1877-1962 (Salt Lake City, UT : Project Gutenberg, 2023)
"Ten Years After: A Reminder" by Philip Gibbs is a historical account written in the early 20th century, reflecting on the aftermath of World War I. The book examines the profound changes in society and politics a decade after the war, addressing the disillusionment and societal upheavals that followed the initial enthusiasm for the conflict. Gibbs illustrates the impact of the war on various nations, particularly focusing on Britain and France. At the start of the book, the author sets the stage by recalling the "spiritual tremor" felt as nations were thrust into the cataclysm of World War I. Gibbs describes the state of mind of people before the war began, emphasizing the prevailing sense of peace and security that was shattered by the onset of conflict. He reflects on the contrasting emotions of horror and determination as nations mobilized for war, driven by a noble sense of duty, and portrays how the realities of trench warfare and loss transformed those initial ideals into a complex legacy of bitterness and disillusionment in the years following the war. (This is an automatically generated summary.)
Foreword -- The world war -- The uncertain peace -- The present perils -- The hope ahead.
Release date is 2023-12-26
Bob Taylor, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: World War, 1914-1918; World War, 1914-1918 -- Peace; World War, 1914-1918 -- Influence